Strategi Bisnis Pada Kelompok Usaha Batu Bata Di Kelurahan Limbung Kecamatan Bajeng - Rezki Putri Amalia; Agung Widhi Kurniawan; TenriSayu Puspitaningsih Dipoatmodjo (Journal of Management and Social Sciences, 2023)
Rezki Putri Amalia’s 2023. “Business Strategy in Brick Business Group in Limbung Village. Guided by Mr. Agung Widhi Kurniawan ST. MM. and Mrs. TenriSayu Puspitaningsih Dipoatmodjo SE, MM. This research aims to find out and analyze the business strategy of the Brick Craftsman Business Group in Limbung Village, Bajeng District, Gowa Regency and to find out the opportunities and challenges faced by Brick Craftsman Businesses in Limbung Village, Bajeng District, Gowa Regency. The number of informants in this research was 6 people as brick entrepreneurs in Limbung Village, Bajeng District, Gowa Regency. The data analysis used is SWOT analysis. The results of the research show that the business strategy of brick craftsmen in Limbung sub-district, Bajeng sub-district, Gowa Regency is expanding market share and increasing the quality of brick products. Opportunities in running a brick business in the Limbung sub-district, Bajeng District, Gowa Regency are that the product for making house stones is brick and the demand for bricks is quite high. The challenges faced by brick craftsmen in the Limbung sub-district, Bajeng sub-district, Gowa Regency, are uncertain weather and the emergence of many new business-based competitors.